2022
DOI: 10.1097/gme.0000000000001976
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and the menopause transition in a cohort of midlife New Zealand women

Abstract: Objective: Knowledge surrounding the link between childhood adversity and reproductive outcomes at midlife is limited. The present study examined the relationship between childhood maltreatment (childhood sexual abuse [CSA], childhood physical punishment [CPP]), and menopause status at age 40.Methods: Data were gathered from female members of the Christchurch Health and Development Study, a longitudinal birth cohort of 1,265 individuals (630 females) born in Christchurch, New Zealand in 1977. Menopause status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Only a few studies, however, have assessed the association between childhood adversity and age at menopause. Data from the 1977 New Zealand birth cohort showed that women at the age of 40 years who experienced severe forms of child sexual abuse were twice as likely to be perimenopausal or postmenopausal when compared with those who were not exposed to child sexual abuse 16 . In the same study, childhood physical punishment did not significantly increase the odds of being perimenopausal or postmenopausal 16 .…”
Section: Discussionmentioning
confidence: 83%
“…Only a few studies, however, have assessed the association between childhood adversity and age at menopause. Data from the 1977 New Zealand birth cohort showed that women at the age of 40 years who experienced severe forms of child sexual abuse were twice as likely to be perimenopausal or postmenopausal when compared with those who were not exposed to child sexual abuse 16 . In the same study, childhood physical punishment did not significantly increase the odds of being perimenopausal or postmenopausal 16 .…”
Section: Discussionmentioning
confidence: 83%
“…Model 1 was controlled for age at matching, race and ethnicity, maternal education level, and marital status. Model 2 was further adjusted for potential confounders based on prior knowledge, measured at diagnosis or reference year or 1 to 5 years prior, including category of BMI (underweight, normal weight, overweight, or obese), [36][37][38] age at menarche (continuous), [12][13][14] parity (0 to 1 or 2 or more children), smoking (never, past, or current), [15][16][17] alcohol drinking (0, 0.1 to 10, or more than 10 grams per day), [39][40][41] physical activity (continuous), [42][43][44] childhood abuse (yes or no), [9][10][11] vitamin D intake (by quantile), and calcium intake (by quantile). [45][46][47] We focused on the associations with early menopause and moderate or severe VMS in the following analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Early natural menopause and bothersome vasomotor symptoms (VMS) are challenging issues during menopause transition. [6][7][8] PMDs, early menopause, and VMS share risk factors (eg, childhood abuse, [9][10][11] earlier pubertal development, [12][13][14] and smoking [15][16][17] ), suggesting common etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer population-based prospective studies have examined associations between CSA and outcomes in mid to late adulthood. In midlife (ages 31-44), data from the Christchurch Health and Development Study and (US) National Longitudinal Study of Adolescent to Adult Health show associations between CSA and higher risk for physical (Duncan et al, 2019), mental (Bell et al, 2019), sexual (Cleland et al, 2022), and economic problems (Assini-Meytin et al, 2022). In middle age, data from the 1958 (British) National Child Development Study (Power & Elliott, 2005) show associations between CSA and higher risk for premature mortality between ages 45 and 58 (Rogers et al, 2021), as well as specific indicators of poorer physical health (physical functioning and self-rated health, Archer et al, 2017;high glycated hemoglobin, Li et al, 2019; health risk behaviors and faster age-related gains in body mass index, Power et al, 2015), mental health (composite psychopathology measure, Clark et al, 2010;suicidal ideation, Stansfeld et al, 2017), and economic (lack of assets, benefit use, financial insecurity, and low socioeconomic status, Pinto Pereira et al, 2017) outcomes.…”
Section: Introductionmentioning
confidence: 99%